School Violence and Educational Outcomes in Tanzanian Secondary Schools: The Mediating Role of Mental Health - Janeth Kigobe; Florian Scharpf; Lucas Wissmann; Tobias Hecker (Journal of Interpersonal Violence, 2026)
Violence at school, perpetrated by teachers and peers, is associated with poorer academic performance. However, association patterns remain unclear in high-violence, socially tolerant contexts. The role of student mental health in this dynamic also warrants closer examination. We investigated direct and indirect associations between teacher violence and peer victimisation, mental health (problems, quality of life), and educational outcomes (grades, absenteeism from attendance records). We studied 524 students from 16 secondary schools in 4 regions of Tanzania. Data came from self-report questionnaires and school records. We used structural equation modelling. Teacher violence and peer victimisation were directly associated with higher absenteeism (teacher b= .17, p < .05; peer b = .13, p < .05). Teacher violence was also directly associated with lower academic performance (b = −.12, p < .05), whereas peer victimisation was not. Both forms of violence were indirectly associated with lower grades via mental health difficulties (teacher indirect b = -.07, 95% CI [-.12, -.04]; peer indirect b = -.11, 95% CI [-.18, -.06]). Peer victimisation also showed an indirect association with lower grades via reduced quality of life (b =-.04, 95% CI [-.09, -.01]). The findings indicate distinct but overlapping association patterns linking school violence to educational outcomes. Reducing violence and strengthening student mental health supports may improve academic engagement and achievement.